Thermodynamic properties of 2-mercapto-, 2, 5-dimethyl- and 2-mercapto-5-methyl-1, 3, 4-thiadiazole. (February 2022) - Silva, Ana L.R.; Gonçalves, Jorge M.; Morais, Victor M.F.; Ribeiro da Silva, Maria D.M.C.
Graphical abstract: Highlights: Combustion enthalpies have been determined by rotating-bomb combustion calorimetry. Sublimation enthalpies derived from Calvet microcalorimetric and Knudsen effusion methods. Gas-phase enthalpies of formation were obtained experimentally and computationally. Thermodynamic stability of the compounds in crystal and gas phases was evaluated. Activation energies for the thiol-thione tautomeric equilibria were calculated. Abstract: The focus of this work is the establishment of energetic-structural correlations of compounds containing a pentagonal heterocyclic ring with different substituents, and consequent contribution on the assessment of their thermodynamic stability and a thorough insight on the thiol-thione tautomeric equilibrium. In this work we report an experimental and computational thermochemical study of three mercaptothiadiazoles: 2-mercapto-1, 3, 4-thiadiazole, 2-mercapto-5-methyl-1, 3, 4-thiadiazole and 2, 5-dimethyl-1, 3, 4-thiadiazole. The experimental data were determined mainly from calorimetric techniques and from effusion method. Thermochemical properties such as the enthalpies of formation, both in crystalline and gaseous phases, the enthalpies of fusion and of sublimation of each compound, as well as the Gibbs energies of formation were derived. Thus, the methyl-substituted thiadiazole is the more stable species in both gaseous and crystalline phases. In addition, quantum chemical calculations were carried out for those isolated molecules. This approach confirms the thione form as the predominant tautomer for the mercaptothiadiazoles. Finally, the activation energies of the tautomeric equilibrium of the mercaptothiadiazoles were calculated in the gas-phase, aqueous and dimethylsulfoxide solutions, showing that the thiol → thione single hydrogen transfers are quite unfavourable reactions in gas phase and in a presence of polar solvents.